45th Lithuanian National Physics Conference. October 25-27, 2023 Program and abstracts of presentations - Matijošius, Aidas; Maldžius, Robertas; Kuliešaitė, Miglė (Vilnius University Proceedings, 2023)
The publication presents the program of the Lithuanian National Physics Conference, traditionally held every two years, as well as abstracts of oral and poster presentations.